2017
DOI: 10.1039/c6tc04136a
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 perovskite nanocrystals as highly selective and sensitive spectrochemical probes for gaseous HCl detection

Abstract: A rapid and facile gaseous anion-exchange reaction between CsPbBr3 perovskite nanocrystals and HCl vapor was carried out under the ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 32 publications
3
67
0
Order By: Relevance
“…On the one hand, changing the halide compositions of nanocrystals is an effective method to obtain IMH perovskites with different bandgaps and optical absorptions . To achieve this goal, several studies have reported the synthesis of different colloidal CsPbX 3 nanocrystals by adding different or mixed PbX 2 salts in the process of the reaction .…”
Section: Synthesis Of Imh Perovskitesmentioning
confidence: 99%
“…On the one hand, changing the halide compositions of nanocrystals is an effective method to obtain IMH perovskites with different bandgaps and optical absorptions . To achieve this goal, several studies have reported the synthesis of different colloidal CsPbX 3 nanocrystals by adding different or mixed PbX 2 salts in the process of the reaction .…”
Section: Synthesis Of Imh Perovskitesmentioning
confidence: 99%
“…We have compared our result with those of two of the recently reported studies. 21,47 First, in these two studies, the authors have synthesized CsPbBr 3 via the hot-injection method under an inert atmosphere condition. This is different from the way we have synthesized CsPbBr 3 , i.e., via the IRTOA method.…”
Section: R) †)mentioning
confidence: 99%
“…5 More recently, metal halide perovskites, which demonstrate attractive opto-electronic properties for photovoltaic applications, 24 have also been tested as sensing materials. In this case, reversible variations of their uorescence, phosphorescence or chemical resistivity upon applying an external stimulus due to intercalation processes, surface absorption, trap passivation or ion exchange have been reported and used for temperature, 25 humidity, 26-28 gas [29][30][31][32][33][34][35][36] and metal ion [37][38][39] sensing.…”
Section: A Introductionmentioning
confidence: 99%
“…35 Despite the large variety of colloidal synthesis procedures for nanomaterials of high crystallinity quality and nely tuned size, shape, and composition, [40][41][42][43][44][45] only a few examples have been reported for sensing applications by using such materials. Among them, nanostructured metal halide materials have been used for sensing metal ions (copper or mercury), 37,39 gases (hydrochloric acid or oxygen) 33,34 and humidity. 26 According to our knowledge there is no sensor based on metal halide nanostructures for ozone gas sensing.…”
Section: A Introductionmentioning
confidence: 99%